2015
DOI: 10.1186/s13104-015-1040-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system lymphoma in a rheumatoid arthritis patient treated with methotrexate: a case report

Abstract: BackgroundRheumatoid arthritis is a systemic inflammatory disease characterized by synovitis and the destruction of articular structures in multiple joints. Methotrexate is recommended as an anchor drug for rheumatoid arthritis treatment to achieve the therapeutic goal of reducing damage to joints and improving clinical score. However, several studies have shown that methotrexate has been associated with the development of lymphoproliferative disorders, namely methotrexate-associated lymphoproliferative disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In the present case, we performed an open biopsy of the right temporal lesion. Biopsy sites of primary CNS MTX-LPD cases including the present case were the cerebrum (7/10), medulla (1/10), skin (1/10), and cervical lymph node (1/8; Table 1 ) In two cases (Cases 5 and 6), cervical lymph node or skin were biopsied rather than the CNS lesion 11 , 12) ; the authors concluded that the CNS lesions and biopsy sites were from the same origins, because after stopping MTX, these lesions regressed.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the present case, we performed an open biopsy of the right temporal lesion. Biopsy sites of primary CNS MTX-LPD cases including the present case were the cerebrum (7/10), medulla (1/10), skin (1/10), and cervical lymph node (1/8; Table 1 ) In two cases (Cases 5 and 6), cervical lymph node or skin were biopsied rather than the CNS lesion 11 , 12) ; the authors concluded that the CNS lesions and biopsy sites were from the same origins, because after stopping MTX, these lesions regressed.…”
Section: Discussionmentioning
confidence: 87%
“…Of the eight cases of cerebral MTX-LPD, seven (including our case) presented as multiple lesions; only one case presented as a solitary lesion. 7 , 8 , 10 , 11 , 13 15) One case with medullary LPD presented with a solitary mass, 9) and a case with hypertrophy of the dura mater presented as intravascular large B-cell lymphoma (IVLBCL). 12) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the potential coexistence of PML and other conditions, such as MTX-related lymphoproliferative disorder. In most cases of MTX-related lymphoproliferative disorder, multiple masses are detected on MRI ( 19 , 20 ). However, a case of multiple lesions without a mass on MRI has been reported ( 21 ), which is similar to the FLAIR and T2-weighted imaging findings in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we searched, there had been no report on MTX–LPD in the orbital area, which was seen in this present case (5). Central nervous lesions were reported in eight cases and were in various sites (e.g., cerebellum, medulla oblongata, subdural, and so forth), except in the pituitary (14, 15, 16, 17, 18, 19). Although we were not able to histopathologically confirm the MTX–LPD etiology of the pituitary lesion in this case, the pathologic background of pituitary lesion and the other lesions were likely the same because the same pathologic subtype had been reported in biopsy specimens of the other lesions and the pituitary lesion developed simultaneously with the other lesions.…”
Section: Discussionmentioning
confidence: 99%